2018
DOI: 10.1007/s00167-018-4988-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased valgus laxity in flexion with greater tibial resection depth following total knee arthroplasty

Abstract: Increased tibial resection depth is associated with significantly greater valgus laxity when tested in positions from 30° to 90° of flexion, despite stability in extension. Greater than 5° of laxity was identified with a tibial resection of 14 mm. When a tibial bone cut of 14 mm or greater is necessary, as may occur with severe preoperative coronal plane deformity, it is recommended to consider the use of a constrained knee prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Sappey-Marinier has demonstrated that an increased tibial resection depth is associated with significantly greater laxity in valgus between 30 and 90°of flexion, particularly with a tibial resection ! 14 mm [32]. Increasing the tibial resection could jeopardize the medial collateral ligament and could complicate TKA revision if required.…”
Section: Inverse Kinematic Alignment Principlesmentioning
confidence: 99%
“…Sappey-Marinier has demonstrated that an increased tibial resection depth is associated with significantly greater laxity in valgus between 30 and 90°of flexion, particularly with a tibial resection ! 14 mm [32]. Increasing the tibial resection could jeopardize the medial collateral ligament and could complicate TKA revision if required.…”
Section: Inverse Kinematic Alignment Principlesmentioning
confidence: 99%
“…Van Opstal et al demonstrated that on average 67% of the PCL insertion was removed in routine primary knee arthroplasty, especially with increasing posterior slope 23,24 . Patients are also at risk of valgus instability in flexion when the tibia is cut more distally, as demonstrated by Sappey-Marinier et al 25 .…”
Section: Resultsmentioning
confidence: 91%
“…One of the concerns regarding the KA and rKA is that balancing is often achieved by re-cutting the tibia, with increasingly thicker polyethylene inserts being required. We have previously demonstrated that this approach for balancing leads to increased valgus laxity through an arc of flexion [ 33 ]. For this reason, in FA, the maximum alteration to joint line-height is set within the limits of ±3 mm , and when large gaps are present (for example, 21 mm), we adjust the depth of the cuts through a combination of femoral and tibial alignment adjustment.…”
Section: Introductionmentioning
confidence: 99%